Potential of sucrose and Pennisetum purpureum cv. Cameroon mulch on the management of Meloidogyne javanica and M. incognita - Débora Cristina Santiago; Martin Homechin; Ricardo Montalvan; Alaide Aparecida Krzyzanowski (Brazilian Archives of Biology and Technology, 2005)
The effects of sucrose on motility and infectiveness of juveniles of Meloidogyne javanica were evaluated under laboratory and greenhouse conditions, using brown sugar and crystal sugar. Results showed that crystal and brown sugar solutions reduced motility and promoted morphological alterations of juvenile nematodes in vitro. The increasing dosages of sucrose reduced the number of galls and egg masses in tomato root by reducing the number of infective juveniles. The efficiency of granular sucrose, sucrose solution, with and without elephant-grass mulch, in the reduction of reproduction and final population of M. incognita race 2, were also evaluated. Granular sucrose induced decrease on the numbers of galls and eggs masses per root system as well as on juveniles in the soil. For sucrose solution assay, the best results for reproductive reduction were obtained with 300g of granular sucrose per liter of soil, applied at seven days intervals, associated with elephant-grass mulch. Os efeitos da sacarose sobre a motilidade e a infectividade de juvenis de Meloidogyne javanica foram avaliados em condições de laboratório e casa-de-vegetação, usando açúcar mascavo e açúcar cristal. Os resultados indicaram que as soluções de açúcar mascavo e cristal reduziram a motilidade e promoveram alterações morfológicas em juvenis dos nematóides in vitro. A eficiência da sacarose em grânulos e da sacarose em solução, com e sem a cobertura com matéria vegetal de capim elefante, na redução da reprodução e da população final de M. incognita raça 2 também foi avaliada. A sacarose em grânulos diminuiu os números de galhas e massas de ovos por sistema radicular e também de juvenis no solo. Para o ensaio com sacarose em solução, os melhores resultados para a redução da reprodução foram obtidos com a dose de 300 g de sacarose por litro de solo, aplicada a intervalos de sete dias, juntamente com a cobertura do solo com cobertura de matéria verde de capim-elefante.